SIMULATING SELECTIVE HARVEST AND IMPACT ON AGE STRUCTURE AND HARVEST EFFICIENCY OF MOOSE IN SWEDEN - Kalén, Christer (Lakehead University, 2018)
I simulated selective harvest strategies of moose (Alces alces) using antler point restrictions and protection of cows with calves to assess the impact of these strategies on population age structure and potential harvest efficiency (proportion of allowed shooting opportunities). The post-hunt, adult bull:cow ratio was held constant throughout the simulations, but age structure of the bull cohort was allowed to vary. The simulation showed that protecting bulls with few antler points (<5) reduced the average bull age in the post-hunt population, whereas protecting bulls with more points (4 – 8) yielded a higher average age. Regardless of type, restrictions caused a measurable drop in harvest efficiency, and subsequently, substantially more hunting days to achieve the harvest quota. Only 33% and 55% of the bulls in the population were eligible for harvest under the <5 points and 4-8 points restrictions, respectively. For cows, the post-hunt, average age was unaffected when cows accompanied by calves were protected during the first 3 weeks; likewise, harvest efficiency was unaffected by harvest restrictions on cows. However, restrictions protecting reproductive cows reduced harvest efficiency of calves, making it more difficult to reach calf harvest quotas. I suggest that antler point and cow hunting restrictions be abandoned in favour of sex-differentiated harvest quotas.